Integrated Land Use System (ILUS) - Koh, Gee Kum (1990)
The concept of ILUS was conceived in the early 1980s. A system study team was then set up by the Civil Service computerisation Group to study the overall computerised needs of the Ministry of National Development (MND) in Singapore. It was established that there was a need for an integrated land and building system for planning purposes. In 1982, funds were given for a 5-year study programme to look into the scope and functional requirements of the land information system. This marked the beginning of the ILUS project.